2017
DOI: 10.1177/0971721817702294
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Entrepreneurship amid Youth in Windhoek’s Informal Settlements: A Namibian Case

Abstract: Considering the high unemployment rate among Namibian youth and a lack of job opportunities, the promotion of entrepreneurship has gained wider attention in the country. A number of initiatives have been started such as entrepreneurship trainings and workshops, business idea competitions, etc. All these aim to inspire young people to think of alternative income sources. As part of a two-year funded community outreach research and development (R&D) project, we have investigated participatory approaches to engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…Surprisingly, access was restricted to tourism, green spaces, safety, and disaster prevention. This contrasts with the findings of Winschiers-Theophilus et al [89], which focused on tourism and green spaces. Limited studies have focused on fire safety, and many residents in Windhoek emphasised this because of the hot weather in summer and the use of wood as a source of heat energy with the potential for fire outbreaks in informal settlements [72].…”
Section: Discussion-general Issues From a Renewed Framework For Impro...contrasting
confidence: 89%
See 1 more Smart Citation
“…Surprisingly, access was restricted to tourism, green spaces, safety, and disaster prevention. This contrasts with the findings of Winschiers-Theophilus et al [89], which focused on tourism and green spaces. Limited studies have focused on fire safety, and many residents in Windhoek emphasised this because of the hot weather in summer and the use of wood as a source of heat energy with the potential for fire outbreaks in informal settlements [72].…”
Section: Discussion-general Issues From a Renewed Framework For Impro...contrasting
confidence: 89%
“…This also shows lapses in the urban resilience structures of the communities. Despite the opportunities for tourism and the use of green spaces, as Windhoek is a city for tourists [89], there is no access to tourism or green space facilities in the neighbourhoods studied. Xu et al [87] identified residents' coping styles with the risk posed by a disaster, including the variables found in Figure 8.…”
Section: Access To Servicesmentioning
confidence: 99%
“…In 2014 Namibia University of Science and Technology (NUST) established a long-term collaboration with marginalised youth in Havana, an informal settlement in Windhoek, Namibia, to co-design digital services aimed at improving the well-being of community members (Winschiers-Theophilus et al 2017). National and institutional ethical approval was granted for the project as well as sub-activities, such as the one presented in this paper.…”
Section: Rationale For Design Interventionmentioning
confidence: 99%
“…The narrower definition associates entrepreneurship education with a specific course aimed at training young people to start their own business, while the wider definition focuses on general skills that all students should learn and that are considered helpful in preparation for life in general (Fejes et al, 2018). Previous studies have cited different objectives and purposes of entrepreneurship education, including: to acquire knowledge and skills; to identify and stimulate entrepreneurial drive, talent and skill; to encourage self-employment; to encourage new start-ups and other entrepreneurial ventures; and to impart the necessary skills to promote the creation of SMEs (Alberti et al, 2004;Winschiers-Theophilus et al, 2017;Johansen and Lundhaug, 2016).…”
Section: Literature Review Entrepreneurship Educationmentioning
confidence: 99%
“…Although most entrepreneurship programmes and courses in tertiary education are offered at university level, some initiatives and interventions are also emerging in the vocational training centres. Furthermore, a number of entrepreneurial programmes and courses have been developed and are offered at various private and accredited smaller training institutions (April, 2015;Winschiers-Theophilus et al, 2017).…”
mentioning
confidence: 99%